Engaging with the Private Sector for Noncommunicable Disease Prevention and Control: Is it Possible to Create "Shared Value?" - Téa E. Collins; Svetlana Akselrod; Lina Mahy; Vladimir Poznyak; Daria Berlina; Arian Hatefi; Luke Allen (Ubiquity Press, 2023)
Noncommunicable diseases (NCDs) are the leading cause of premature mortality worldwide. Corporate interests are sometimes well-aligned with public health, but profiteering from the consumption of products that are known to be the major contributors to the noncommunicable disease burden undermines public health. This paper describes the key industry actors shaping the NCD landscape; highlights the unhealthy commodities' impact on health and the growing burden of NCDs; and outlines challenges and opportunities to reduce exposure to those risk factors. Corporations deploy a wide array of strategies to maximize profits at the expense of health, including sophisticated marketing techniques, interference in the policy-making process, opposition and distortion of research and evidence, and whitewashing of health-harming activities through corporate social responsibility initiatives. There can be no shared value for industries that sell goods that harm health irrespective of consumption patterns (such as tobacco and likely alcohol), so government actions such as regulation and legislation are the only viable policy instruments. Where shared value is possible (for example, with the food industry), industry engagement can potentially realign corporate interests with the public health interest for mutual benefit. Deliberate, careful, and nuanced approaches to engagement are required.